Generic Structure and Copy Elements in Indonesian Cosmetics Copy Ads on Instagram - Husna Conia Ismayati (Universitas Pendidikan Indonesia (UPI), 2018)
The study aims to elaborate the generic structure of Indonesian cosmetics advertisements on Instagram and copy elements distribution in the generic structure. Theoretical framework in the study is based on Hasan's (1989a) theory of analyzing genre to elaborate the genre of copy ads on Instagram. Moreover, the copy elements proposed by Maslen (2007) which include feature, benefit, and call to action are also utilized to examine the generic structure in depth using the perspective of copywriting. Qualitative method is used in current research employing descriptive statistics to analyze data. Data collection comprises 32 copy ads from 8 Indonesian-written Instagram accounts which specify in promoting cosmetics products on Instagram. Results show that the genre of Indonesian cosmetics copy ads on Instagram manifested three types of generic components including 'opening', 'product description', and 'closing'. As for the copy elements distribution in the generic structure, benefit and call to action are found mostly in 'opening', feature and benefit are in 'product description', and call to action is found mostly in 'closing'. Further research can be conducted to analyze the data obtained from diverse sources and languages in order to increase the credibility of results in current research. Keywords: Generic structure, generic components, copy elements, copy ads, Instagram